2011
DOI: 10.1002/jwmg.227
|View full text |Cite
|
Sign up to set email alerts
|

Abundance trends of American martens in Michigan based on statistical population reconstruction

Abstract: Estimating the dynamics of furbearer populations is challenging because their elusive behavior and low densities make observations difficult. Statistical population reconstruction is a flexible approach to demographic assessment for harvested populations, but the technique has not been applied to furbearers. We extended this approach to furbearers and analyzed 8 yr of age‐at‐harvest data for American marten (Martes americana) in the Upper Peninsula of Michigan. Marten abundance estimates showed a general downw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 16 publications
0
52
1
Order By: Relevance
“…Some of the most recent developments require estimation of initial animal cohort abundance as a parameter [3], [4], [7], [8], or as a latent variable [5] in a frequentist or Bayesian framework, respectively. Recently, models for statistical population reconstruction (SPR) of harvested large game animals have been developed that utilize the same likelihood-based inference techniques, but instead consider estimating animal abundance following optimization, outside of the likelihood framework with a Horvitz-Thompson-type estimator, which adjusts the observed harvest count by the estimated probability of harvest in accordance with the assumption of a binomial sampling scheme [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the most recent developments require estimation of initial animal cohort abundance as a parameter [3], [4], [7], [8], or as a latent variable [5] in a frequentist or Bayesian framework, respectively. Recently, models for statistical population reconstruction (SPR) of harvested large game animals have been developed that utilize the same likelihood-based inference techniques, but instead consider estimating animal abundance following optimization, outside of the likelihood framework with a Horvitz-Thompson-type estimator, which adjusts the observed harvest count by the estimated probability of harvest in accordance with the assumption of a binomial sampling scheme [9].…”
Section: Introductionmentioning
confidence: 99%
“…The older two age classes, then, represent a combination of animals born in the previous year that survived to the current year, as well as the adults that survived an additional year or more following their first year. In comparison to fully aged harvests of many big game animals, this represents a considerable loss of cohort data upon which the SPR models of Gove et al [3], Skalski et al [4], Skalski et al [8], and Gast et al [9] rely. On the other hand, Skalski et al [10] found little loss in precision when big game population reconstruction was based on pooling adult harvest information for age classes 3+.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species remains protected from trapping in Wisconsin despite population sizes sufficient to allow harvesting in neighboring Minnesota and Michigan (Skalski et al 2011, Williams et al 200). The Michigan population has been slowly expanding its range and has supported a modest recreational trapping season since 2000 (Skalski et al 2011). …”
Section: (Burns and Honkala 1990)mentioning
confidence: 99%
“…This approach is appealing because age‐at‐harvest data has been collected at low cost for many game species. Statistical population reconstruction has been applied to a variety of species, including greater sage‐grouse ( Centrocercus urophasianus ; Broms et al ), martens ( Martes americana ; Skalski et al ), wild turkeys ( Meleagris gallopavo ; Clawson et al ), and grizzly bears ( Ursus arctos ; Hatter et al ). Statistical population reconstruction has also been used to estimate mountain lion abundance in British Columbia, Canada (Hatter ), and northeastern Oregon (Clawson ) and North Dakota, USA (Johnson et al ).…”
mentioning
confidence: 99%